2019
DOI: 10.1177/1455072518800189
|View full text |Cite
|
Sign up to set email alerts
|

Gambling involvement, type of gambling and grade point average among 18–29-year-old Finnish men and women

Abstract: Aims: This study explores the associations between gambling involvement, type of gambling, at-risk and problem gambling (ARPG) and register-based grade point average (GPA), among Finnish people aged 18-29 years (N ¼ 676). It is assumed that high gambling involvement and engaging in certain types of gambling are linked to ARPG, and that low school achievement is positively associated with these measures. Methods: A nationwide cross-sectional random sample was collected in 2015. The data were weighted based on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Finally, an important role for social adaptation and academic success is played by the student's beliefs about his/her own ability to plan and organize school activities (academic self-efficacy). In this regard, pathological gamblers are more likely to have poor school performance, as demonstrated in both cross-cutting studies (Latvala et al, 2019) and longitudinal studies (Winters et al, 2002). In gambling studies, self-efficacy has been defined primarily as the individual ability to avoid involvement in problem gambling (Barbaranelli et al, 2017).…”
Section: Self-efficacymentioning
confidence: 99%
“…Finally, an important role for social adaptation and academic success is played by the student's beliefs about his/her own ability to plan and organize school activities (academic self-efficacy). In this regard, pathological gamblers are more likely to have poor school performance, as demonstrated in both cross-cutting studies (Latvala et al, 2019) and longitudinal studies (Winters et al, 2002). In gambling studies, self-efficacy has been defined primarily as the individual ability to avoid involvement in problem gambling (Barbaranelli et al, 2017).…”
Section: Self-efficacymentioning
confidence: 99%
“…For the groups of habitual, social and heavy gamblers, the vast majorities were males ( 26 ). A Finnish study of people aged 18–29 showed that frequent gambling, playing several game types, online gambling and at risk-or problem gambling occurred more often among males than females ( 27 ). Because of the larger gambling involvement and the fact that men generally take more risks the women ( 28 ), a suggested explanation for the gender association with measures to control gambling is that men more often than women need and therefore also actually use these features or measures to control their gambling more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is gambling an activity that makes people lose a lot of money, but it also harms the wellbeing of the gamblers and their next of kin and has been shown to involve several types of stratifying effects ( Oksanen, Sirola, Savolainen, & Kaakinen, 2019 ). Gambling-related harm disadvantageously affects the socioeconomically weak in particular, and in the study by Latvala, Alho, Raisamo, and Salonen (2019) people who perform less well at school measured in register data’s Grade Point Average (GPA) are shown to be more likely to gamble more frequently and to prefer certain kinds of games.…”
Section: Habits and Adherent Harmsmentioning
confidence: 99%